TiO 2/Al 2O 3 membrane reactor equipped with a methanol recovery unit to produce palm oil biodiesel - Baroutian, S.; Aroua, M.K.; Abdul Raman, Abdul Aziz; Sulaiman, N.M.N. (John Wiley & Sons, 2012)
In this study, the central composite design of the response surface methodology was employed to investigate the effects of reaction temperature, catalyst concentration and cross flow circulation velocity on the production of biodiesel in a TiO 2/Al 2O 3 membrane reactor. High-quality palm oil biodiesel was produced by combination of alkali transesterification and separation processes in the ceramic membrane reactor. The optimum conditions for the conversion of palm oil to biodiesel in the ceramic membrane reactor were as follows: 70Â°C reaction temperature, 1.12wt catalyst concentration and 0.211cms - 1 cross flow circulation velocity. The physical and chemical properties of the produced biodiesel were determined and compared with the standard specifications. Â© 2010 John Wiley & Sons, Ltd.